ANALISIS ISI PERUT DAN UKURAN TUBUH ULAR JALI (Ptyas mucosus) - Irvan - Sidik (Masyarakat Zoologi Indonesia, 2006)
Sidik, I. 2006. Stomach contents and body size in common rat snake (Ptyasmucosus). Zoo Indonesia. Vol. 15 (2): 121-127. Climatic changed from drought (dry)to rainy (wet) season is represent the active habit for foraging food of common ratsnake (Ptyas mucosus). Farm, garden and rice fields which still widespread in centraland east Java provinces area have common known by resident as living place of thissnake. This study was to examine the stomach contents of live common rat snakesusing dissecting and flushing stomach contents that were modified. Liquid componentsuch as juicy composite was identified from stomach contained carbohydrate (14.7%),cellulose (30.85%), and lignine (12.43%). Whereas solid materials consist of insect(12.76%), partly body of toads, frogs and skinks, and mammals fur. Unidentifiedmaterials (29.26%) composed of very small particles, most probably grains and plantseeds. Ecology data concerning habitat availability of common rat snake was used ascomparison data to extrapolate of foraging area. Generally, common rat snake get itsfood source from agriculture area. This matterial was known from mixture of element ofplant fiber in composite of digestible animal. There wass possibility that amphibian asa important interconnected food with their ecology.